One Step Quantum Key Distribution Based on EPR Entanglement - Li, Jian (Sci Rep, 2016)
A novel quantum key distribution protocol is presented, based on entanglement and dense coding and allowing asymptotically secure key distribution. Considering the storage time limit of quantum bits, a grouping quantum key distribution protocol is proposed, which overcomes the vulnerability of first protocol and improves the maneuverability. Moreover, a security analysis is given and a simple type of eavesdropper’s attack would introduce at least an error rate of 46.875%. Compared with the “Ping-pong” protocol involving two steps, the proposed protocol does not need to store the qubit and only involves one step.